Pore healing effect of laser polishing and its influence on fatigue properties of 316L stainless steel parts fabricated by laser powder bed fusion. (December 2022) - Panov, Daniil; Oreshkin, Oleg; Voloskov, Boris; Petrovskiy, Victor; Shishkovsky, Igor
Abstract: Potential application of the additive manufactured (AM) parts is still inhibited by poor fatigue properties. In this work, we applied laser polishing to simultaneously reduce factors that affected the fatigue properties, such as surface roughness and sub-surface porosity. Our findings show that significant porosity reduction in sub-surface area can be achieved with one scan pass without major deterioration of surface quality. The surface quality, sub-surface layer porosity and mechanical properties of the laser polished with pore removing pass and conventionally laser polished samples are compared with as-built samples. Sub-surface porosity reduction effect mainly depends on remelted layer depth. Thus the porosity reduction up to 90% in the sub-surface layer can be achieved. The surface quality of the samples is evaluated by Scanning Electron Microscopy, Optical and Stylus profilometry. Surface roughness decrease is at least 90%. The quasi-static and High Cycle Fatigue (HCF) mechanical characteristics of the samples are studied. The fatigue limit increases by at least 82% after laser polishing. The fatigue limit of samples with introduced pore removing pass is slightly lower than the limit for the conventionally laser polished samples. Difference in fracture mechanics of post-processed and as-built samples after HCF tests is described. Highlights: Laser polishing improves roughness, fatigue strength and sub-surface density. Laser polishing with high power scan pass results in sub-surface layer densification. Depth of the laser remelted layer defines rate of sub-surface porosity reduction. Laser polishing increases fatigue strength of as-built SS316L LPBF parts.